DES-ultrasonication treatment of cellulose nanocrystals and the reinforcement in carrageenan biocomposite - Nur Amalina, Ramli; Fatmawati, Adam; Ries, Michael E.; S. Fatimah, Ibrahim (Elsevier Ltd, 2024)
CNCs are intensively studied to reinforce biocomposites. However, it remains a challenge to homogeneously disperse the CNC in biocomposites for a smooth film surface. Mechanochemical treatment via ultrasonication in deep eutectic solvent (DES) generated a stable dispersion of CNC before incorporation into carrageenan biocomposite. Shifted peaks of choline chloride (ChCl) methylene groups to 3.95–3.98 ppm in 1H NMR indicated a formation of eutectic mixture between the hydrogen bond acceptor (HBA) and hydrogen bond donor (HBD) at the functional group of CH3···OH. The swelling of CNC in the DES was proven by the formation of intermolecular H-bond at a length of 2.46 Å. The use of DES contributed to a good dispersion of CNC in the solution which increased zeta potential by 43.2 % compared to CNC in deionized water. The ultrasonication amplitude and feed concentration were varied for the best parameters of a stable dispersion of CNC. The crystallinity of 1 wt% of CNC at 20 % sonication amplitude improved from 76 to 81 %. The high crystallinity of CNCDES resulted in an increase in film tensile and capsule loop strength of Carra-CNCDES by 20.7 and 19.4 %, respectively. Improved dispersion of CNCDES reduced the surface roughness of the biocomposite by 21.8 %. H-bond network in CNCDES improved the biocomposite properties for an ingenious reinforcement material.